The importance of neighbourhood parks in enhancing the mental and physical well-being of low-cost housing residents in the aftermath of the COVID-19 pandemic - Mohmmad Zin, Harith; Abu Bakar, Nor Azlina; Azlan, Aznida (MAJ - Malaysia Architectural Journal, 2023)
The COVID-19 crisis resulted in a notable decline in the mental and physical well-being of residents in low-cost housing, primarily due to restricted living space and limited access to recreational activities. The significance of neighbourhood parks has increased in recent times due to their ability to fulfil the outdoor recreational requirements, thereby promoting mental well-being, provided that the attributes of the parks meet the residents’ expectations. Thus, the present research examines the characteristics of neighbourhood parks that have an impact on the well-being of low-cost housing inhabitants during the period of post-COVID-19 movement limitations. The investigation utilised a qualitative research design consisting of three case studies conducted in low-cost housing areas located in Lembah Pantai, Kuala Lumpur. A purposive sampling technique was employed to select 15 participants for semi-structured interviews. Additionally, observations were carried out at various times and days to enhance the richness of the data. Thematic analysis was conducted on the interviews using ATLAS.ti v22, whereas manual analysis was performed on the field observation photographs. The research determined that the attribute of adaptability holds the highest significance, given its capacity to adjust and assimilate unforeseen disruptions, such as the COVID-19 pandemic. This study is to guide the planning and implementation of neighbourhood parks in low-cost housing areas, with a focus on adapting to the post-COVID-19 criteria.